Lady with erotic preference for diapers. Issue 2 (23rd November 2016) - Cernovsky, Zack; Bureau, Yves
Abstract : A patient in her 20s was referred to us for psychological assessment due to her depression and suicide attempts. She mentioned being anorgasmic except when diapered and emphasized her erotic preference for diapers. Her childhood included maternal deprivation in an impecunious family headed by an irritable physically disabled father on social assistance. Given the maternal deprivation in childhood, her erotic fixation on diapers parallels the emotional attachment to diapers observed by Harlow in mother deprived infant monkeys. Etiological hypotheses should also include the paradigm of avoidance learning from theories of behavior therapy. Our patient does not wish to change her sexual preference: in such cases, fetishism is not considered as an illness by DSM5. However, she needs to be treated for pathological levels of depression with suicidal ideation and low self-esteem.